2016
DOI: 10.1002/ccd.26871
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐induced encephalopathy following cardiac catheterization

Abstract: M a i l i n g A d d r e s s : F r e d e r i c o T. U l t r a m a r i @@@@@@@@@@@@@@@@@@@@@@@@@@@ It is estimated that 6,000 and 2,000 cardiac catheterization procedures per million inhabitants/year are performed in Western countries for diagnostic and therapeutic purposes. In order to perform these procedures, 1,800 tons of iodine are required all over the world to manufacture contrast media (CM). The number of procedures that require the use of contrast media (or dye) has increased over time, and the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
107
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 50 publications
2
107
0
9
Order By: Relevance
“…Typical radiological findings include cerebral oedema and cortical enhancement. Since the first clinical description in 1970, there have been 52 cases of CIE following cardiac catheterisation reported in the literature [16]. Here, we report a highly probable case of CIE post-CAG with no radiological findings on CT of the head and with spontaneous recovery.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Typical radiological findings include cerebral oedema and cortical enhancement. Since the first clinical description in 1970, there have been 52 cases of CIE following cardiac catheterisation reported in the literature [16]. Here, we report a highly probable case of CIE post-CAG with no radiological findings on CT of the head and with spontaneous recovery.…”
Section: Introductionmentioning
confidence: 81%
“…Measuring the Hounsfield units (HU) on CT as an indicator of the density of the lesion in doubtful cases can assist in distinguishing haemorrhage from contrast extravasation since contrast presents a higher attenuation (80–160 HU) than blood (40–60 HU) [19]. The most frequently reported head CT finding in the literature is cortical or subcortical enhancement, but it has been reported that the enhancement resolves in 25 h in most cases [16]. Diagnosis of CIE is normally made by finding typical radiological signs on non-contrast CT in a symptomatic patient after excluding thromboembolic and haemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%
“…CM extravasation could mimic radiologically SAH which is likely to occur in cases in which more than one revascularization is performed [6]. The density of the lesion measured in Hounsfields units (HU) could be a useful distinguishing characteristic, which is confirmed in a recently published review of 53 published cases of "contrast induced encephalopathy" noting that blood density is ranging between 40 and 60 HU and contrast media usually between 100 and 300 HU [7]. Magnetic resonance imaging (MRI)-derived apparent diffusion coefficient (ADC) was shown as a reliable imaging modality that differentiates contrast extravasation from cerebral ischemia [8].…”
Section: Discussionmentioning
confidence: 99%
“…CIE is a reversible neurological complication associated with contrast administration 1. In acute ischaemic or haemorrhagic stroke, abnormalities remain on follow-up imaging, whereas they disappear in CIE. CIE after PCI is an extremely rare complication 1. We emphasise the need for increased awareness of CIE in patients with acute coronary syndrome undergoing PCI.…”
mentioning
confidence: 99%